2005
DOI: 10.1002/ijc.20669
|View full text |Cite
|
Sign up to set email alerts
|

Unmasking immunosurveillance against a syngeneic colon cancer by elimination of CD4+ NKT regulatory cells and IL-13

Abstract: We have previously observed a novel role of natural killer T (NKT) cells in negative regulation of antitumor immune responses against an immunogenic regressor tumor expressing a transfected viral antigen. Here, we investigated whether hidden spontaneous antitumor immunosurveillance, in the absence of a vaccine, could be revealed by disruption of this negative regulatory pathway involving CD4؉ NKT cells and interleukin-13 (IL-13), in a murine pulmonary metastasis model of a nontransfected, nonregressor, syngene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
68
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(78 citation statements)
references
References 53 publications
8
68
0
Order By: Relevance
“…In addition, a soluble form of IL-13R 2 can prevent IL-13-mediated suppression of tumor immunosurveillance. 26,27 Therefore, i.t. introduction of IL-13R 2 chain into established tumors may efficiently lead to activation of an antitumorigenic response and tumor immunosurveillance in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, a soluble form of IL-13R 2 can prevent IL-13-mediated suppression of tumor immunosurveillance. 26,27 Therefore, i.t. introduction of IL-13R 2 chain into established tumors may efficiently lead to activation of an antitumorigenic response and tumor immunosurveillance in tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…14 IL-13 is a pleiotropic and Th2-dominated immune regulatory cytokine, 19,20 which plays a central role in allergic asthma [21][22][23] and mediates diverse responses during helminth infection. 24,25 It is critical for tumor immunosurveillance 26,27 and modulates apoptosis or tumor cell growth. 28,29 Two different components of the IL-13 receptor have been identified, which are known as IL-13R 1 chain [30][31][32] and IL-13R 2 chain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Paradoxical role of NKT cells in tumor immunity. With this background in which the predominance of the literature suggested that type I invariant NKT cells were protective against tumors based on a Th1 bias, it was surprising to find that NKT cells could also suppress tumor immunosurveillance based on their production of the Th2 cytokine IL-13 (93)(94)(95)(96)(97), even though they contributed to asthma or protected against some autoimmune diseases based on a Th2 bias. Recurrence of a murine regressor tumor was found not to occur if CD4 ϩ regulatory cells were depleted, and these CD4 ϩ cells were found to be CD1d-restricted NKT cells (93), not CD4 ϩ CD25 ϩ Treg cells (98).…”
Section: Regulatory Role Of Type I Nkt Cells In Autoimmunity Andmentioning
confidence: 99%
“…It is clear that NKT cells that are protective against tumors are skewed toward Th1 cytokines, while type ІІ NKT cells suppress tumor immunosurveillance based on their production of Th2 cytokines [53] . The potentially opposite effect of these two subsets of NKT cells was also determined in CD1d KO mice lacking both subtypes of NKT cells with decreased production of Th1 and Th2 cytokines but Jα18 KO mice lacking only NKT cells with reduced IFN-γ during murine schistosomiasis [54] .…”
Section: Polarization Of Th1 and Th2 Cytokines In Nkt Cellsmentioning
confidence: 99%